Saxitoxin Group Toxins Accumulation Induces Antioxidant Responses in Tissues of Mytilus chilensis, Ameghinomya antiqua, and Concholepas concholepas during a Bloom of Alexandrium pacificum - Javiera Oyaneder-Terrazas; Diego Figueroa; Oscar F. Araneda; Carlos García (MDPI AG, 2022)
Saxitoxin (STX) group toxins consist of a set of analogues which are produced by harmful algal blooms (HABs). During a HAB, filter-feeding marine organisms accumulate the dinoflagellates and concentrate the toxins in the tissues. In this study, we analyze the changes in antioxidant enzymes and oxidative damage in the bivalves Mytilus chilensis and Ameghinomya antiqua, and the gastropod Concholepas concholepas during a bloom of Alexandrium pacificum. The results show that during the exponential phase of the bloom bivalves show an increase in toxicity and activity of antioxidant enzymes (superoxide dismutase, catalase, glutathione peroxidase, and glutathinoe reductase, p < 0.05), while in the gastropods, increased activity of antioxidant enzymes was associated with the bioaccumulation of toxins through the diet. At the end of the bloom, decreased activity of antioxidant enzymes in the visceral and non-visceral tissues was detected in the bivalves, with an increase in oxidative damage (p < 0.05), in which the latter is correlated with the detection of the most toxic analogues of the STX-group (r = 0.988). In conclusion, in areas with high incidence of blooms, shellfish show a high activity of antioxidants, however, during the stages involving the distribution and bioconversion of toxins, there is decreased activity of antioxidant enzymes resulting in oxidative damage.